The Margins of the Rational Man: Fluid Identities in Eighteenth-Century Biography - Over, William (Text Matters: A Journal of Literature, Theory and Culture, 2012)
This study will explore the Enlightenment conception of the individual of reason, its attempted formulations in actor biographies, and its ultimate denial by the reality of human identity as multiple, fluid, and dialogical. Such fluidity sought to overcome the marginal status of the stage player through the embodiment of rational models of personality. Some stage celebrities, most notably David Garrick, were offering themselves as public models of identity for the new age of reasoned discourse. This involved the presentation before the public of stage performers as fully realized individuals. However, the unavoidable problem was that presenting an individual, even a renowned stage star, as a living paradigm of the enlightened person of reason would prove elusive. Aside from the inherent contradiction of locating any perfected stereotype in an actual person, the qualities making an individual in full conformity to his or her “reason” did not match the particular cultural qualities demanded for a successful eighteenth-century middle-class Englishman or Englishwoman. Nonetheless, by the last quarter of the eighteenth century, significant advances were made both within the particular profession of acting and before the onstage and offstage public. The acting profession was moving quickly and for the first time in England away from its marginalized status to offer respected agents for cultural change. The new genre of actor biographies as well contributed to this more fully realized formulation of the modern individual.